Canonical Wnt Signaling Pathway on Polarity Formation of Utricle Hair Cells - Di Deng; Xiaoqing Qian; Binjun Chen; Xiaoyu Yang; Yanmei Wang; Fanglu Chi; Yibo Huang; Yu Zhao; Dongdong Ren (Neural Plasticity)
As part of the inner ear, the vestibular system is responsible for sense of balance, which consists of three semicircular canals, the utricle, and the saccule. Increasing evidence has indicated that the noncanonical Wnt/PCP signaling pathway plays a significant role in the development of the polarity of the inner ear. However, the role of canonical Wnt signaling in the polarity of the vestibule is still not completely clear. In this study, we found that canonical Wnt pathway-related genes are expressed in the early stage of development of the utricle and change dynamically. We conditionally knocked out β-catenin, a canonical Wnt signaling core protein, and found that the cilia orientation of hair cells was disordered with reduced number of hair cells in the utricle. Moreover, regulating the canonical Wnt pathway (Licl and IWP2) in vitro also affected hair cell polarity and indicated that Axin2 may be important in this process. In conclusion, our results not only confirm that the regulation of canonical Wnt signaling affects the number of hair cells in the utricle but also provide evidence for its role in polarity development.